Active Ageing Index as an evaluation tool for policy towards elderly - Jurek, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The level of activity of old people is measured by the special index called Active Aging Index. The main purpose of the article is to present this index as a tool to evaluate policy toward old people. Author focused on three main issues: (1) description of the AAI structure; (2) presentation of the relationship between AAI and a policy towards elderly; (3) discuss the value of AAI in European Union countries. Used method is a desk research, that is analysis if existing data including literature, reports and statistical studies.